PENGEMBANGAN APLIKASI PENYEWAAN SEPEDA MOTOR BERBASIS ANDROID UNTUK MENINGKATKAN EFISIENSI LAYANAN BOSS SEWA MOTOR PURWOKERTO: DEVELOPMENT OF AN ANDROID-BASED MOTORCYCLE RENTAL APP TO IMPROVE THE EFFICIENCY OF BOSS SEWA MOTOR PURWOKERTO SERVICES - Alif Tarmad; Mohammad Imron (LPPM Universitas Abdurrab, 2026)
The tourism industry in Purwokerto City has triggered an increase in demand for transportation services, especially motorcycle rentals. However, Boss Sewa Motor Purwokerto still faces efficiency constraints because the booking process is carried out manually via WhatsApp, which causes response delays and unsystematic data documentation. This research aims to develop an Android-based motorcycle rental application to digitalize business processes, improve the data management structure for admins, and simplify booking access for renters. The system development method used is the Waterfall method, which includes the stages of data collection, requirements analysis, system design, implementation, testing, and maintenance. System design was carried out using Unified Modeling Language (UML) tools, DFD, ERD, and interface design using Figma. The research resulted in the “Boss Sewa Motor Purwokerto” app, built using Flutter technology and the Firebase database to manage 15 motorcycles (8 Honda Beat and 7 Honda Vario). Functional testing using the Black Box Testing method shows that all main features, from account management to the real-time booking system, operate stably without technical failures. In conclusion, this application successfully replaced the manual system, improved operational efficiency, and provided more transparent and practical services for users and managers of Boss Sewa Motor.